Analisis Maqashid Syariah Sebagai Konsep Dasar dalam Penetapan Fatwa MUI No: 21/DSN-MUI/X/2001 tentang Pedoman Umum Asuransi Jiwa Syariah - Rosida, Ika Nazilatur (Journal of Industrial and Syariah Economics, 2023)
This study aims to analyze the maqashid sharia as a basic concept in fatwa No: 21/DSN-MUI/X/2001 about the general guidelines for sharia life insurance. The regulation on the general guidelines of the Sharia life insurance company in Indonesia is regulated at fatwa No: 21/DSN-MUI/X/2001. The creation of a law or a fatwa has a purpose or a maqahid sharia in its stipulation. This study is literature research. the data collected by the library, reading, and taking notes. The compilation of data on this study is from online books, journals, scientific articles, and the literature review that contains the concepts of maqahid sharia, DSN MUI, and sharia insurance. The results of the study show that there are aims and objectives in determining the law or fatwa which refers to five things that are maintained, namely: guaranteeing the preservation of religion, guaranteeing the preservation of the soul, guaranteeing the preservation of reason, ensuring the preservation of offspring, guaranteeing the maintenance of property as a guide in fatwa No: 21/DSN-MUI/X/2001 regarding general guidelines for sharia life insurance.